2022
DOI: 10.1007/s11255-022-03193-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: mortality rates of patients on hemodialysis and peritoneal dialysis

Abstract: Objective Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection might have a higher mortality rate in patients with end-stage renal disease due to immunosuppression. This study investigates the mortality rates of SARS-CoV-2 infection and the factors affecting mortality among patients who were on maintenance hemodialysis and continuous ambulatory peritoneal dialysis. Materials and methods A total of 200 patients, including 157 maintenance hemodialysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
2
16
2
2
Order By: Relevance
“…The COVID-19-related fatality rate among PD patients is poorly understood. Most studies included only a limited number of PD patients, ranging from two to thirty in each trial ( 2 , 13 , 20 23 ). We demonstrated that the early COVID-19-related fatality rate for PD patients was at least comparable to those of PD patients from the other studies ( 2 , 13 , 20 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19-related fatality rate among PD patients is poorly understood. Most studies included only a limited number of PD patients, ranging from two to thirty in each trial ( 2 , 13 , 20 23 ). We demonstrated that the early COVID-19-related fatality rate for PD patients was at least comparable to those of PD patients from the other studies ( 2 , 13 , 20 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies included only a limited number of PD patients, ranging from two to thirty in each trial ( 2 , 13 , 20 23 ). We demonstrated that the early COVID-19-related fatality rate for PD patients was at least comparable to those of PD patients from the other studies ( 2 , 13 , 20 23 ). In a large multicenter European registry consisting of 768 patients on maintenance dialysis and only 4% of study participants on chronic PD therapy, Hillbrands et al observed a fatality rate of 30% in the PD group at 28 days after COVID-19 diagnosis, compared to a fatality rate of 25% for all dialysis patients ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that PD patients had less COVID-19 infection rate than HD patients [ 14 ]. There are other reports indicating that mortality in PD patients was higher than HD patients, probably due to some comorbidities; in our case, PD patients had more diabetes, but not older age [ 15 ].…”
Section: Discussionmentioning
confidence: 50%
“…5,6 To date only few and relatively small series of PD patients with COVID-19 have been described, 7,8 some as part of articles that also describe other dialysis patient groups. 2,[9][10][11][12] An European Renal Association (ERA) Registry report compared 125 PD patients with 3126 HD patients and showed that there was no statistically significant difference between PD and HD patients, although the adjusted probability of death at day 28 was higher in PD patients (21.6%) than in HD patients (18.0%). 2 Unfortunately, details of the disease course and treatment were not available in this cohort.…”
Section: Introductionmentioning
confidence: 99%